Improving ROP management: insights from a comparative analysis of screening and treatment modalities in a tertiary hospital, Pakistan - Muhammad Moin; Aisha Azam; Lubna Siddiq Mian; Ashal Pal; Rutaab Kareem; Noor Us Sehar (BMC Ophthalmology)
Abstract Background The principal objective of our study is to evaluate the characteristics of babies with type 1 ROP, screening practices and treatment trends in a tertiary care centre in Pakistan. Methods This prospective study at Mayo Hospital, Lahore (July 2022–July 2024), included 89 preterm infants with type 1 ROP, selected using non-probability sampling. Infants were categorized based on international (GA < 32weeks or BW < 1500 g) and local screening criteria (GA < 35 weeks or BW < 2000 g), and treatment outcomes were evaluated across three groups: Anti-VEGF, combination therapy (Anti-VEGF followed by laser), and laser therapy. Statistical analysis was performed using SPSS version 27.0, significance was set at p < 0.05. Results Out of 355 infants screened, 89 (25.1%) met the inclusion criteria for type 1 ROP. The cohort included 55 males (61.8%) and 34 females (38.2%), with a mean gestational age of 31.31 weeks and a mean birth weight of 1602.25 g. Zone 1 ROP was found in 36% of cases, associated with lower birth weight (P = 0.029) and earlier gestational age (P = 0.037), while Zone 2 ROP, found in 64%, was linked to higher birth weight and later gestational age. Zone 1 infants were more likely to receive anti-VEGF or combination therapy, whereas Zone 2 infants predominantly received laser therapy (p < 0.000). Preterm infants (born before 32 weeks) mostly received Anti-VEGF or combination therapy, while those with higher birth weights primarily received laser therapy (p < 0.010). Among the treated babies, 63 (70.8%) met international screening criteria and were more likely to have Zone 1 ROP and receive Anti-VEGF or combination therapy. Conversely, 26 (29.2%) did not meet these criteria, had predominantly Zone 2 ROP and were more likely to receive laser therapy (p = 0.007). Conclusion International screening criteria effectively identify severe type 1 ROP cases, particularly Zone 1, which often require Anti-VEGF therapy. Local criteria capture additional cases, predominantly Zone 2, which are more likely to need laser treatment. These findings highlight the need for tailored screening and treatment approaches to improve ROP management and outcomes for preterm infants.